2019
DOI: 10.24191/jchs.v4i2.7551
|View full text |Cite
|
Sign up to set email alerts
|

Leptin: a pleitropic factor in physiology

Abstract: Leptin, a 16 kDa protein and a product of the ob/ob gene, has a tertiary structure similar to that of a cytokine. It is primarily secreted by white adipose tissue and its levels in the blood correlate positively with percentage body fat. Leptin was first identified in 1994 as a major factor that regulated food intake and energy balance. Leptin in the circulation exists either as a free monomeric hormone or bound to its soluble receptor. Its serum levels usually range from 0.5 to 37.7 ng/ml in males and 2.0 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 229 publications
2
7
0
Order By: Relevance
“…14 Leptin levels in our study are positively related to BMI and this is consistent with results obtained from a study performed on Greek men where the levels of leptin in men with a BMI > 30 kg/m 2 were 170% higher than in men with a BMI < 27 kg/m 2.11 Our results support that leptin is an important marker of obesity 27,46 where its expression in obese subjects is, on average, 2-fold higher than that in lean individuals. 26,49 Moreover, our results comply with a previous cross-sectional study conducted on Jordanian youth males that revealed obese and overweight subjects had high leptin levels and these levels were positively associated with parental history of T2DM. 50 The levels of serum leptin in NW and OW groups were not affected by CCR; moderate coffee consumers had similar levels to those who are heavy coffee consumers.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…14 Leptin levels in our study are positively related to BMI and this is consistent with results obtained from a study performed on Greek men where the levels of leptin in men with a BMI > 30 kg/m 2 were 170% higher than in men with a BMI < 27 kg/m 2.11 Our results support that leptin is an important marker of obesity 27,46 where its expression in obese subjects is, on average, 2-fold higher than that in lean individuals. 26,49 Moreover, our results comply with a previous cross-sectional study conducted on Jordanian youth males that revealed obese and overweight subjects had high leptin levels and these levels were positively associated with parental history of T2DM. 50 The levels of serum leptin in NW and OW groups were not affected by CCR; moderate coffee consumers had similar levels to those who are heavy coffee consumers.…”
Section: Discussionsupporting
confidence: 91%
“…20 Besides that, it was suggested there is a J-shaped relationship between CCR and health outcomes in which moderate consumption is beneficial, whereas heavy consumption is detrimental. 21,22 Leptin, an adipokine hormone, 25,26 plays an important role in the regulation of appetite, energy expenditure by inhibiting hunger and reducing food intake, which in turn diminishes the body weight (BW) and fat storage in adipocytes. 25,27 Moreover, leptin is involved in the regulation of sexual maturity and reproduction, cardiovascular functions, metabolisms, and stress response.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations